On the Border of Ancient Greek and Barbarian worlds. Sindian Arms and Armour of the 5th-4th centuries BC - Горончаровский, Владимир (Acta Archaeologica Lodziensia, 2021)
На рубеже античного и варварского миров: вооружение Cиндов V-IV вв. до н.э. In the early period of the history of the Cimmerian Bosporus, on their eastern borders the Sindoi held a dominant position among the Barbarian tribes. Contacts with the Greek colonists eventually influenced the development of the Sindian panoply of weaponry, for the study of which archaeological sources are of major importance. First of all come the finds of weapons from the tombs of the Sindian aristocracy in the Semibratnie tumuli. The earliest of them (No. 2: ca. 450-440 BC) has produced a set of weapons, in which Oriental influences are discernable (particularly a sword of the “Sindian-Meotian type” and body armor made of iron scales with gold plating). The emergence of plate armor with shoulder-straps among the Sindoi one can be link with the Greek influence. In barrow No. 4 (ca. 440-430 BC) the armor was supplemented by a round plate with the image of the Gorgon Medusa. The plate greaves copied Greek knemidoi. At the same time until the turn of the 5th -4th centuries BC a shield with a stacked coating of iron strips, as was used as in the nomadic environment of the Black Sea Coast. There is the obligatory bow and gorytos with arrows in the equipment of the noble warrior. Meanwhile helmets were not found in any of the graves. Since the beginning of the 4thcentury BC an absolute novelty was the use of Greek swords (the hilt of machaira and the bronze lower part of the scabbard of a xiphos). At some stage the use of allied cavalry supplied by the Sindoi considerably strengthened the Bosporan kingdom in opposition to threats emanating from the edge of Barbarian lands.